REASSESSMENT OF THE STEREOTYPES IN SPEECH BEHAVIOR OF UZBEKS/ENGLISH PEOPLE - Abdukodirova Damira (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article discusses the issues of reassessment of stereotypes in speech acts of Uzbek and English people. One of the indicators of relations in stereotypes of interethnic speech in language, the need to study the rules of speech etiquette, which is an important component of culture and integral part of the general system of speech behavior in society is emphasized.